Implikatur Yang Bermakna Kebencian Pada Anime Kaguya Sama: Love is War (Kajian Pragmatik) - Dewi Saparina H; Sandi Dwi Rizki Al Sunandar (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
Sandi Dwi Rizki Al Sunandar .2021. “Implicature contains Hate meaning in Kaguya Sama: Love is War” Thesis of Japanese Literature Study, Faculty of Letters, National University of PASIM Bandung. The discussion in this study is about Implicature that contain Hate meaning in Kaguya Sama: Love is War uses pragmatics studies. The purposes of making this study to be able to know about implicature contains Hate in Kaguya Sama: Love is War. Main source in this study is using 8 episodes of Season 1 Kaguya Sama: Love Is War, capable to analyzes illocutionary of act, describes the implicatur that contain hate meaning and capable to describes the type conversation of implicature in Kaguya Sama: Love Is War in episode 1 to 8. This study is a descriptive research. At the data collection stages, the writer uses the note-taking method, translating data, reducing data that has hate meaning in term of implicate. The result is 20 of data represents: For the shape of act, contain 8 Representative, 11 expressive and 1 Directive.in total,all of implicature contains hate about 8 datas. And, the type of conversation of implicature in this study has 14 general conversational implicature and 6 special conversational implicature.